MENGENAL HUMAN PAPILOMA VIRUS SEBAGAI FAKTOR RESIKO KANKER SERVIKS - Kusnul, Zauhani; Fitriyah, Erna Tsalatsatul; Sasmito, Nanang Bagus (LPPM STIKes Bahrul Ulum Jombang, 2018)
Cervical cancer is a problem that deserves great attention in order to improve the health status of the community, especially women's health. WHO data states that cervical cancer is the fourth most common cancer cases among women. In Indonesia cervical cancer is the highest case of cancer in Indonesia, that is equal to 0,8% o. The most important risk factor of cervical cancer is the infection of human papillomavirus (HPV) of persistent high risk type. HPV infection triggers a variety of mechanisms that result in increased proliferation of infected cells, gene mutations and lateral expansion leading to the formation of cancerous issue.